Bringing Human Rights Education to US Classrooms: Exemplary Models from Elementary Grades to University by Susan Roberta Katz and Andrea McEvoy Spero (Eds.) - Bennett, Michael (Radical Teacher, 2015)
A Review of Bringing Human Rights Education to US Classrooms: Exemplary Models from Elementary Grades to University.